2012
DOI: 10.7763/ijcee.2013.v5.471
|View full text |Cite
|
Sign up to set email alerts
|

Application of Solar Powered Automatic Water Pumping in Turkey

Abstract: microprocessors and microcontroller programming, serial and parallel active power filters, and photovoltaic systems, photovoltaic irrigating systems, RF control and communications, and distance education material design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 18 publications
0
25
1
1
Order By: Relevance
“…The procedure to elaborate a computer program, photo-irrigation, to correctly and straight forwardly design a PV installation to power an irrigation pumping system for a given crop at a given site was described by Cuadros et al [40]. Dursun and Ozden [41] designed an automatic drip irrigation of dwarf cherry trees system with solar powered Brushless DC Motors, in Zile District of Tokat Province of Turkey. The results showed that the use of this photo-irrigation system will be able to contribute to the socio-economic development in the Tokat region.…”
Section: Solar Pv Pumping Systemmentioning
confidence: 99%
“…The procedure to elaborate a computer program, photo-irrigation, to correctly and straight forwardly design a PV installation to power an irrigation pumping system for a given crop at a given site was described by Cuadros et al [40]. Dursun and Ozden [41] designed an automatic drip irrigation of dwarf cherry trees system with solar powered Brushless DC Motors, in Zile District of Tokat Province of Turkey. The results showed that the use of this photo-irrigation system will be able to contribute to the socio-economic development in the Tokat region.…”
Section: Solar Pv Pumping Systemmentioning
confidence: 99%
“…Worldwide, 15% of total energy consumption in crop production is for pumping irrigation water (Dursun & Ozden, 2012…”
Section: Introductionmentioning
confidence: 99%
“…The study computed monthly mean values from (2004 -2007) in Terengganu state (Malaysia), models are estimating on a horizontal surface and found out a good source from those models in case lost the data of radiation in that period, a new linear model which used was (H/Ho= 0.2207 + 0.5249) based on Angstrom model. M. Dursun and S. Ozden [6] had been used an automatic irrigation system to irrigate an area of the plants with cherry trees by two motors, the first was placed inside a deep well to transfer a water in the tank. The second motor has a task to transfer the water from the tank to the drip irrigation system.…”
Section: Introductionmentioning
confidence: 99%